2014
DOI: 10.1007/s11524-014-9894-3
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability to Food Insecurity in Urban Slums: Experiences from Nairobi, Kenya

Abstract: Food and nutrition security is critical for economic development due to the role of nutrition in healthy growth and human capital development. Slum residents, already grossly affected by chronic poverty, are highly vulnerable to different forms of shocks, including those arising from political instability. This study describes the food security situation among slum residents in Nairobi, with specific focus on vulnerability associated with the 2007/2008 postelection crisis in Kenya. The study from which the dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
128
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(161 citation statements)
references
References 23 publications
(21 reference statements)
14
128
2
1
Order By: Relevance
“…Using longitudinal data spanning 6 years from households in two informal settlements in Nairobi, we observed high levels of food insecurity -only 27 % of households were food secure. Levels of food insecurity were nearly threefold that of the national average of 26 % in 2013 (Dietz et al 2014) and consistent with previous studies conducted in the same context (Faye et al 2011;Kimani-Murage et al 2014) and in other contexts (Musyoka et al 2010;Birhane et al 2014). Urban agriculture is limited and urban households, including the poor, depend on food supplies from rural areas and the ability to pay in a cash-based economy (Kimani-Murage et al 2014).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Using longitudinal data spanning 6 years from households in two informal settlements in Nairobi, we observed high levels of food insecurity -only 27 % of households were food secure. Levels of food insecurity were nearly threefold that of the national average of 26 % in 2013 (Dietz et al 2014) and consistent with previous studies conducted in the same context (Faye et al 2011;Kimani-Murage et al 2014) and in other contexts (Musyoka et al 2010;Birhane et al 2014). Urban agriculture is limited and urban households, including the poor, depend on food supplies from rural areas and the ability to pay in a cash-based economy (Kimani-Murage et al 2014).…”
Section: Discussionsupporting
confidence: 87%
“…Levels of food insecurity were nearly threefold that of the national average of 26 % in 2013 (Dietz et al 2014) and consistent with previous studies conducted in the same context (Faye et al 2011;Kimani-Murage et al 2014) and in other contexts (Musyoka et al 2010;Birhane et al 2014). Urban agriculture is limited and urban households, including the poor, depend on food supplies from rural areas and the ability to pay in a cash-based economy (Kimani-Murage et al 2014). The first three years were characterized by high levels of food insecurity and coincided with the post-election period in 2008 that was marked by political turmoil and the hunger strikes of 2007-2008 due to increased world food prices and inflation.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Research shows that African urban households from all socioeconomic classes may obtain as much as 90% of their calories from purchased food [27] and spend as much as 50% of their income on food [12]. Urban food security is more integrated in global and regional economies when compared to rural areas, which benefits and burdens urban food security.…”
Section: Urban Food Systemsmentioning
confidence: 99%
“…A survey of more than 3000 households in two slums in Nairobi, Kenya-a part of the wider Urban Health and Demographic Surveillance System, which involved 70,000 individuals within nearly 30,000 households-found that 85% of households were food insecure and 50% were severely food insecure [11]. Additional research from South Africa has found that 80% of poor urban dwellers in Cape Town can be classified as moderately or severely food insecure [12]. Similarly, a recent survey from Tamale, Ghana, a regional capital with fewer than 250,000 residents, found that more than 50% of respondents were mildly to severely food insecure [13].…”
Section: Introductionmentioning
confidence: 99%